PENGARUH PERHATIAN ORANG TUA, KETERAMPILAN GURU MENGAJAR DAN AKTIVITAS BELAJAR - Pepi Elian; Yon Rizal; Tedi Rusman (FKIP Unila, 2013)
This research aim to know the influence of parent attention, student perception about teacher skill of teacher in teaching and learning activity to IPS Terpadu. Method used in this research is descriptive method of verifikatif with the approach of ex post facto and survey. The result of research for use, (1) there is positive and significant influences of parent attention to IPS Terpadu leaning result of SMP Negeri 2 Way Kenanga of Tulang Bawang Barat at Academic Year 2012/2013, (2) there is positive and significant influences about student perception of teacher skill in teaching to IPS Terpadu learning result at SMP Negeri 2 Way Kenanga in Tulang Bawang Barat at Academic Year 2012/2013, (3) there is positive and significant influences of learning activity to IPS Terpadu learning result at SMP Negeri 2 Way Kenanga of Tulang Bawang Barat at Academic Year 2012/2013, (4) there is positive and significant influences of parent attention, student perception about teacher skill in teaching, and learning activity to IPS Terpadu at SMP Negeri 2 Way Kenanga of Tulang Bawang Barat at Academic Year 2012/2013. Key words: Attention, Teacher Skill, Activity.